Pembelajaran Sejarah Berbasis Nilai-nilai Serat Wedhatama untuk Menumbuhkan Etika dan Moral Siswa - Renny Pujiartati; Hermanu Joebagio; Sariyatun Sariyatun (Yupa: Historical Studies Journal, 2017)
Serat Wedhatama is a serat that is written by Mangkunegara IV, where in there are the cultural values of their nation. Their culture is then necessary to transform students through education, in particular the historical studies. This paper is a part of Research and Development (R&D) using the model of the Borg & Gall development model oriented learning history based Serat Wedhatama values to improve ethics and morals in students and habitual in educational institutions. In the first stage measures undertaken include: (1) the mapping ethical values and morals in the Serat Wedhatama through the process of hermeneutics; (2) a description of the learning history at State High School 5 Surakarta; (3) the formulation of draft models learning history based Serat Wedhatama values. The results of this study are: (1) produce deconstruction of ethical values and morals in Serat Wedhatama, (2) description of the condition of learning history at a high school in Surakarta, (3) a draft model of a learning history based values of Serat Wedhatama